Keabsahan Penerapan Upaya Paksa Perampasan Aset dalam Tindak Pidana Penganiayaan Berat : Studi Kasus Putusan No.297/Pid.B/2023/PN Jkt.Sel - Trias Saputra; Ickbal Hofifi Bairuroh; Rafid Ibrahim; Joddy Mulya Setya Putra (JURNAL HUKUM PELITA, 2025)
Resreach discusses providing Restitution through Forced Efforts to Seize Assets from Defendant Mario Dandi which went viral in the mass media, the fraudster was subjected to Forced Efforts to Seize Assets in the form of a Rubicon car to fulfill his obligation to pay Restitution to the victim's child, Davit Ozora. The defendant was charged with the article on Serious Assault as regulated in the Criminal Code (KUHP). Restitution is the right of every victim of a crime who experiences material or immaterial losses as regulated in Article 7A of Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. Restitution is the responsibility of the perpetrator or a third party who must be redeemed by the perpetrator for criminal acts that cause losses to the victim. For example, in the District Court Decision No.297 / Pid.B / 2023 / PN Jkt.Sel with the fraud of Mario Dandi, which by the court decision was imposed a Criminal in the form of Forced Efforts to Seize Assets. This study aims to describe several errors in the implementation of Restitution. The method used in this research is Juridical-Normative using secondary data or library data (library research) with a Statute Approach and Case Study